2019
DOI: 10.1101/521195
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Circular inference in bistable perception

Abstract: When facing fully ambiguous images, the brain cannot commit to a single percept and instead switches between mutually exclusive interpretations every few seconds, a phenomenon known as bistable perception. Despite years of research, there is still no consensus on whether bistability, and perception in general, is driven primarily by bottom-up or top-down mechanisms. Here, we adopted a Bayesian approach in an effort to reconcile these two theories. Fifty-five healthy participants were exposed to an adaptation o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Importantly, different loops result in different types of aberrant percepts: while ascending loops induce unimodal hallucinations (eg, AH in SCZs), descending loops give rise to multisensory phenomena (eg, synesthesia-like experiences; MMH induced by DMT). 151 Although the former link between ascending loops and SCZs has already been empirically established, 152 the latter between descending loops and psychedelics remains purely theoretical and still needs experimental support.…”
Section: Computational Modelingmentioning
confidence: 99%
“…Importantly, different loops result in different types of aberrant percepts: while ascending loops induce unimodal hallucinations (eg, AH in SCZs), descending loops give rise to multisensory phenomena (eg, synesthesia-like experiences; MMH induced by DMT). 151 Although the former link between ascending loops and SCZs has already been empirically established, 152 the latter between descending loops and psychedelics remains purely theoretical and still needs experimental support.…”
Section: Computational Modelingmentioning
confidence: 99%
“…Evidence linking CI and MMHs comes from work on synesthesia, a perceptual phenomenon whereby stimulation of one modality leads to experiences in another modality 77 and which has been linked to disinhibited feedback from association cortex to sensory cortex. 78 Ongoing research using simulations of drug-induced synesthesia 79 has shown that reverberation of information descending the cortical hierarchy (descending loops) could induce audio–visual experiences in the absence of clear sensory input (cross-modal hallucinations) but also a contamination of one modality by another in the presence of a unimodal stimulus (synesthesia). These 2 features were retained as good candidates for modeling psychedelic-induced subjective experiences using probabilistic approaches.…”
Section: Theoretical Perspectivesmentioning
confidence: 99%
“…A conceivable experiment could use biasing by creating expectation of either a face with low facial height-to-width ratio or with high value of this ratio. (The often used selective, physically produced emphasis of some parts of the face can be used as an experimental control-e.g., Leptourgos et al, 2020. ) In the Gestalt tradition there are different types of cues for perceptual organization and object formation (Wagemans et al, 2012).…”
Section: Discussionmentioning
confidence: 99%